The Effect of Ball Filling Porosity on the Capacity of Torque Transmitted in the Ball Centrifugal Clutch - Turkbay, Ismail (Gazi Univ, 2005)
Centrifugal clutches have two groups according to shape of the friction elements, as centrifugal elements and filling material. The centrifugal clutches with centrifugal elements have a limit because of adjusted ability which is for changing loads and velocities. The centrifugal clutches with filling material are filled completely or partly with filling material depending on the required clutch torque. In ball-centrifugal clutch steel balls are distributed, at equal amount, in the chambers between the housing with paddle wheel and are lubricated with oil. In this study, porosity of ball fillings in prism was calculated theoretically and in the ring of cylinder, porosity of ball fillings was obtained experimentally. The effect of steel ball fillings having constant mass and emptiness factors on the torque transmitted was determined in ball- centrifugal clutch.
Keywords: Ball-centrifugal clutch; slipping torque; emptiness factor; porosity